Single crowns versus conventional fillings for the restoration of root filled teeth - Fedorowicz, Zbys; Carter, Ben; de Souza, Raphael Freitas; Lima Chaves, Carolina de Andrade [UNESP]; Nasser, Mona; Sequeira-Byron, Patrick (Wiley-Blackwell, 2012)
BackgroundEndodontic treatment, involves removal of the dental pulp and its replacement by a root canal filling. Restoration of root filled teeth can be challenging due to structural differences between vital and non-vital root filled teeth. Direct restoration involves placement of a restorative material e.g. amalgam or composite directly into the tooth. Indirect restorations consist of cast metal or ceramic (porcelain) crowns. The choice of restoration depends on the amount of remaining tooth which may influence long term survival and cost. The comparative in service clinical performance of crowns or conventional fillings used to restore root filled teeth is unclear.ObjectivesTo assess the effects of restoration of endodontically treated teeth (with or without post and core) by crowns versus conventional filling materials.Search methodsWe searched the following databases: the Cochrane Oral Health Group's Trials Register, CENTRAL, MEDLINE via OVID, EMBASE via OVID, CINAHL via EBSCO, LILACS via BIREME and the reference lists of articles as well as ongoing trials registries. There were no restrictions regarding language or date of publication. Date of last search was 13 February 2012.Selection criteriaRandomised controlled trials (RCTs) or quasi-randomised controlled trials in participants with permanent teeth which have undergone endodontic treatment. Single full coverage crowns compared with any type of filling materials for direct restoration, as well as indirect partial restorations (e.g. inlays and onlays). Comparisons considered the type of post and core used (cast or prefabricated post), if any.Data collection and analysisTwo review authors independently assessed trial quality and extracted data.Main resultsOne trial judged to be at high risk of bias due to missing outcome data, was included. 117 participants with a root filled premolar tooth restored with a carbon fibre post, were randomised to either a full coverage metal-ceramic crown or direct adhesive composite restoration. At 3 years there was no reported difference between the non-catastrophic failure rates in both groups. Decementation of the post and marginal gap formation occurred in a small number of teeth.Authors' conclusionsThere is insufficient evidence to support or refute the effectiveness of conventional fillings over crowns for the restoration of root filled teeth. Until more evidence becomes available clinicians should continue to base decisions on how to restore root filled teeth on their own clinical experience, whilst taking into consideration the individual circumstances and preferences of their patients.